Pemanfaatan Teknologi ChatGPT untuk Pengembangan Asesmen Pembelajaran Berdiferensiasi bagi Guru-Guru Bahasa Inggris di Kabupaten Lombok Utara - Waluyo, Untung; Soepriyanti, Henny; Elmiana, Dewi Satria; Tsaqiila , Thalia Qaulan; Azzuhri, Rendy Fahmi; Mudrika, Julia Ridha (Jurnal Pengabdian Magister Pendidikan IPA, 2025)
The rapid emergence of Artificial Intelligence (AI), particularly ChatGPT, provides new opportunities for innovation in English Language Teaching (ELT). However, many teachers in rural Indonesia, especially in North Lombok Regency, still struggle to integrate AI tools due to limited digital literacy, minimal training, and inadequate infrastructure. This community service program aimed to enhance teachers’ ability to design differentiated learning assessments using ChatGPT. The program implemented an AI-based digital literacy workshop that combined theoretical and hands-on practice, followed by mentoring and evaluation. Twenty English teachers from the Musyawarah Guru Mata Pelajaran (MGMP) participated in training sessions designed to improve confidence and practical competence in AI-assisted lesson planning and assessment creation. Data were collected through pre–post tests, observation, and reflection reports. Findings reveal significant improvement in teachers’ digital literacy, creativity in assessment design, and collaboration through digital networks. Despite challenges such as unstable internet access and limited facilities, the participants successfully produced AI-based assessment prototypes adapted to their students’ needs. The program demonstrates that AI-integrated teacher training can bridge the gap between pedagogical innovation and classroom practice, empowering teachers to create inclusive and differentiated learning environments.